Case Report: Practical approach to differentiating juvenile parkinsonism of genetic cause and drug-induced parkinsonism in adolescents: a case series and literature review - Grigore, Ioana; Butnariu, Lăcrămioara Ionela; Schreiner, Thomas Gabriel; Lupu, Vasile Valeriu; Lupu, Ancuta; Darie, Ludmila; Prăzaru, Cătălin; Țarcă, Elena; Popa, Setalia; Grigore, Ecaterina (Frontiers in Genetics, 2025)
Juvenile parkinsonism is a disease which is rarely seen in pediatric patients. In addition, drug-induced Parkinson’s syndrome is generally rare in children; however, it represents one of the most severe iatrogenic movement disorders in adults. The authors present one case of genetically confirmed juvenile parkinsonism and two cases of chronic Parkinson’s syndrome induced by psychiatric medication. The aim is to underline the differences between the clinical presentation, laboratory results, and the evolution under treatment. In addition, by reviewing literature data we analyzed the most significant information to describe the differences between these two conditions. Parkinsonian syndromes in pediatric patients and juvenile parkinsonism are difficult to diagnose based solely on clinical presentation because the manifestations are non-specific. Genetic testing and exclusion of other causes is essential for the final diagnosis. Adolescents who are diagnosed with drug-induced parkinsonian syndromes should undergo neurological evaluation, due to the fact that there is a risk of developing idiopathic Parkinson’s disease later during adulthood.